Optimizing Goat Manure Rates and Liquid Organic Fertilizer Concentrations for Solanum melongena L. Physiology and Fruit Output in Surabaya, East Java - Difa Eka Pranoto; Nova Triani; Agus Sulistyono (Universitas Labuhanbatu, 2025)
Background: Purple eggplant (Solanum melongena L.) is a high-value nutritional crop with significant market demand. However, production in Indonesia fluctuated between 2021 and 2023; after reaching a peak of 551,552 tons, yields dropped to 510,749 tons in 2023. This decline is largely attributed to the excessive use of synthetic fertilizers. This study aims to evaluate the interactions and effects of integrating goat manure with various liquid organic fertilizers (LOF) on purple eggplant growth. Furthermore, this research seeks to establish sustainable cultivation practices that reduce chemical dependency in horticulture. Methodology: This research followed a Factorial Randomized Block Design (RBD) with two factors and three replications. The first factor was the goat manure dosage at four levels: 0 g/plant (control), 500 g/plant, 750 g/plant, and 1,000 g/plant. The second factor consisted of four types of liquid applications: NPK 16:16:16 (control), eco-enzyme LOF, banana peel LOF, and cabbage waste LOF. Observation data were analyzed using Analysis of Variance (ANOVA), followed by Tukey’s Honestly Significant Difference (HSD) test at a 5% significance level where significant effects were detected. Findings: The results showed that the combined treatment of goat manure dose of 1,000 g/plant and banana peel LOF gave the best results in the parameters of plant height (46.67 cm), number of leaves (16.33 leaves), total fruit number per plant (11.72 fruits), and total harvest weight per plant (1635.94 grams) compared to other organic combination treatments. Contribution: The combination of goat manure and banana peel liquid organic fertilizer (LOF) emerged as the most effective treatment compared to other organic combinations. This organic treatment resulted in a 28% yield increase over the control. Althought this specific increase was not statistically significant, the study strongly recommends organic fertilizers as a sustainable and eco-friendly alternative to reduce inorganic fertilizer dependency in horticultural farming systems